A mathematical view on dynamics of a prey predator exemplary with C-M functional reaction and diffusion - V. S. N. Murty, A; Madhusudanan, V; N. Srinivas, M (International Journal of Engineering and Technology, 2018)
In this article, we considered an ecosystem with Crowley-Martin functional response. We verified mathematical peculiarities of the model like boundedness, and positive invariance. Analysis of local and global stabilities of the system is also verified. Hopf bifurcation analysis is also carried out by finding the nature of the periodic solution around interior steady state using Taylor’s series. We also studied the diffusion analysis. Numerical simulations are carried out with the help of MATLB.